PENDALAMAN MATERI BUKU BESAR DAN NERACA LAJUR PERUSAHAAN JASA - Wijoyo, Amin; Nicholas Richardson; Cherry Tanichi (Jurnal Serina Abdimas, 2025)
Education about the general ledger and trial balance carried out at SMAN 2 Jakarta is part of the Community Service program involving lecturers and students of Tarumanagara University. This program aims to provide a real contribution to the advancement of education in Indonesia by enriching students' knowledge regarding the accounting recording process, especially in posting to the general ledger and preparing the trial balance. The material was delivered offline on Thursday, March 13, 2025, involving 30 students of SMAN 2 Jakarta. This activity has important value because it provides two main benefits, namely introducing the basic concepts of the general ledger and trial balance and broadening students' understanding of the principles and flow of the accounting cycle. During the activity, students received material exposure from expert teachers, were involved in theoretical discussions regarding the material presented, learned practical steps for posting transactions from the general journal to the general ledger and trial balance, and worked on practice questions to deepen their understanding. It is hoped that this increased understanding will be able to prepare students to face further education and the world of work in the future. As an indicator of the success of this Community Service program, the evaluation results showed that 85% of participants successfully answered the questions correctly in the quiz session guided by the FEB UNTAR team. This achievement is real evidence that the Community Service program is effective in improving student understanding and providing meaningful learning outcomes. ABSTRAK Kegiatan pendalaman materi mengenai buku besar dan neraca lajur yang dilaksanakan di SMAN 2 Jakarta merupakan bagian dari program Pengabdian Kepada Masyarakat (PKM) yang melibatkan dosen serta mahasiswa-mahasiswi Universitas Tarumanagara. Program ini bertujuan untuk memberikan kontribusi nyata terhadap kemajuan pendidikan di Indonesia dengan memperkaya pengetahuan siswa-siswi terkait proses pencatatan akuntansi, khususnya dalam melakukan posting ke buku besar dan penyusunan neraca lajur. Materi disampaikan secara luring pada Kamis, 13 Maret 2025, dengan melibatkan 30 siswa-siswi SMAN 2 Jakarta. Kegiatan ini memiliki nilai penting karena memberikan dua manfaat utama yaitu memperkenalkan konsep dasar buku besar dan neraca lajur serta memperluas pemahaman siswa/i terhadap prinsip dan alur siklus akuntansi. Selama kegiatan, siswa/i menerima paparan materi dari pengajar ahli, terlibat dalam diskusi teoritis mengenai materi yang disampaikan, mempelajari langkah-langkah praktis memposting transaksi dari jurnal umum ke buku besar dan neraca lajur, serta mengerjakan latihan soal untuk memperdalam pemahaman mereka. Diharapkan, peningkatan pemahaman ini mampu mempersiapkan siswa/i dalam menghadapi pendidikan lanjutan dan dunia kerja di masa depan. Sebagai indikator keberhasilan program PKM ini, hasil evaluasi menunjukkan bahwa 85% peserta berhasil menjawab soal dengan tepat dalam sesi kuis yang dipandu oleh tim FEB UNTAR. Capaian ini menjadi bukti nyata bahwa program PKM tersebut efektif dalam meningkatkan pemahaman siswa dan memberikan hasil pembelajaran yang bermakna.